2011
DOI: 10.1523/jneurosci.5884-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PKMζ in Nucleus Accumbens Core Abolishes Long-Term Drug Reward Memory

Abstract: During abstinence, memories of drug-associated cues persist for many months, and exposure to these cues often provokes relapse to drug use. The mechanisms underlying the maintenance of these memories are unknown. A constitutively active atypical protein kinase C (PKC) isozyme, protein kinase M ζ (PKMζ), is required for maintenance of spatial memory, conditioned taste aversion, and other memory forms. We used conditioned place preference (CPP) and conditioned place aversion (CPA) procedures to study the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 57 publications
(99 reference statements)
10
102
1
Order By: Relevance
“…Specifically, if endocytosis of the GluA2-containing AMPA receptors is prevented, then the temporary inactivation of PKMz should have no effect on memory maintenance because this renders the replacement function served by PKMz moot-no replacement is necessary. This hypothesis has been tested and supported in experiments with both brain slices and behavior Li et al 2011). Thus, we used this strategy to determine if our results with ZIP could be related, at least indirectly, to disrupting the role of PKMz in regulating trafficking of GluA2-containing AMPARs.…”
Section: Pkmz Maintains Memories In the Dls And Dmsmentioning
confidence: 83%
See 2 more Smart Citations
“…Specifically, if endocytosis of the GluA2-containing AMPA receptors is prevented, then the temporary inactivation of PKMz should have no effect on memory maintenance because this renders the replacement function served by PKMz moot-no replacement is necessary. This hypothesis has been tested and supported in experiments with both brain slices and behavior Li et al 2011). Thus, we used this strategy to determine if our results with ZIP could be related, at least indirectly, to disrupting the role of PKMz in regulating trafficking of GluA2-containing AMPARs.…”
Section: Pkmz Maintains Memories In the Dls And Dmsmentioning
confidence: 83%
“…However, if it is infused at various intervals after LTP has been induced, established potentiation is reversed, indicating that PKMz is critical for the maintenance of established LTP. Second, when ZIP is injected into brain regions thought to be memory storage sites, behavioral evidence for the memory is lost (Pastalkova et al 2006;Shema et al 2007Shema et al , 2011Serrano et al 2008;Hardt et al 2010;Li et al 2011).…”
Section: Pkmz Maintains Memories In the Dls And Dmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then in which brain regions does GluR2-3Y inhibit the addictive behavior? Previous studies found that the endocytosis of AMPARs containing GluR2 in the NAc plays an important role in the expression of amphetamine-induced behavioral sensitization [21] and the long-term maintenance of mCPP [25]. Moreover, endocytosis in the BLA and in the ventral medial PFC is crucial for the reconsolidation of methamphetamine reward memory [26] and cue-induced heroin-seeking [15], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent exciting findings of erasure of memory traces by a selective antagonist of the protein kinase M zeta (Li et al, 2011;Sacktor, 2011;Shema, Sacktor, & Dudai, 2007) have increased the hope that permanently established neuronal connections could be reorganized later in life. Although these results have been questioned (Lisman, 2011;Volk, Bachman, Johnson, Yu, & Huganir, 2013;Wu-Zhang, Schramm, Nabavi, Malinow, & Newton, 2012), indicating that we do not understand the molecular mechanisms well enough, this line of research might turn out to be very fruitful for the future understanding of the memory-like processes that make compulsive addiction so persistent.…”
Section: Abstinence Relapsementioning
confidence: 99%